Epipelagic copepods in Bahía Cupica, Colombian Pacific: species composition, distribution and temporal variation - Jerez-Guerrero, Mauricio (2017)
The study of changes in abundance and composition of copepod species, at different temporal and spatial scales, help to understand the ecosystems function and how the oceanographic dynamics affects their variability and other resources abundances. Since very few studies have been developed on this group in Colombian Pacific coastal areas, the purpose of this study was to assess the spatial and temporal changes in the copepods community distribution at Cupica Bay, between December 2012 and February 2013. For this, oblique plankton hauls were performed along six transects perpendicular to the coast, in 22 stations, using a Bongo Net (30 cm diameter, 2.1 m large, with mesh size 250 µm and 500 µm) equipped with a flowmeter, during two contrasting oceanographic periods. The results showed significant changes in oceanographic conditions and superficial circulation patterns. Fifty two (52) copepods species were identified, from which thirty five (35) were new records for the Colombian Pacific. The biggest copepod abundance was recorded in February 2013 (28 604 ind. 100 m-3), and small copepods species were the most dominant. During December 2012, species of the order Poecilostomatida were the most abundant (58.2), but during February were the species of the order Calanoida (69.5 %). The community structure and species composition was characterized by five significant groups, three groups during December 2012 and two during February 2013, dividing the bay in different zones. A positive correlation between temperature and copepods assemblages was evident during both periods, but stronger during December 2012. The results suggested that community structure and species composition of resident copepods in North Colombian Pacific neritic zones, are modelled by the intensity of upwelling, superficial local pattern circulation, and continental freshwater discharges in the region. The results are helpful to understand the copepods community structure, and the future studies should attempt to examine other variables (e.g. effect of food available and oxygen concentration dissolved) to improve understanding of copepods structure in the Pacific coast region of Colombia.